Morphological and lectin histochemical studies of the spermatozoa of the lesser mouse deer (Tragulus javanicus) - Prasetyaningtyas, Wahono Esthi; Agungpriyono, Srihadi; Yamamoto, Yoshio; Haron, Abd Wahid; Mohamad Agus, Setiadi; Mokhamad, Fahrudin (Veterinary Association Malaysia, 2006)
The morphology and lectin histochemical property of the spermatozoa of the lesser mouse deer (Tragulus javanicus) were studied using light and scanning electron microscopy. Spermatozoa were small in size and measured 36.52 ± 5.6 μm in length. The head of the spermatozoa was relatively round in shape (5.55 ± 0.8 μm in length and 4.77± 0.5 μm in width). Lectin peanut (Arachis hypogea) agglutinin (PNA) and lectin wheat germ (Triticum vulgaris) nagglutinin (WGA) were positive in the membrane of the acrosomal region, and in the membrane at the anterior part of the acrosomal region and in the tail, respectively. It is suggested that carbohydrates with galactose β1-3, D-N acetylgalactosamine, D-N acetylglucosamine and sialic acid sugar residues may be involved and may have significant roles in the spermatozoa in the lesser mouse deer.